Dislodged Watchman Device Retrieved Using Double Transseptal Sheaths Technique and Reinstalled with LAmbre Device - yafan han; Wang Feifei; Jiasuoer Xiaokereti; Hang Yang; Yanmei Lu; Xianhui Zhou; Yaodong Li; Baopeng Tang (Anatolian Journal of Cardiology, 2022)
In patients with persistent atrial fibrillation (AF) with a high risk of bleeding, left atrial appendage closure (LAAC) has gradually become the best alternative to long-term oral anticoagulant therapy in preventing stroke.1 However, in some patients, the occlusion device falls off because of various reasons, such as improper selection or unstable preinstallation, and constitutes one of the most serious complications of LAAC.2 Here, we report a case of an elderly patient with AF. On the second day after the surgery, her Watchman device fell off. The detached device was retrieved using the double transseptal sheaths technique, and the LAmbre device was installed.